Land Tenure Insecurity as an Investment Incentive: The Case of Migrant Cocoa Farmers and Settlers in Ivory Coast†. (20th September 2018) - Bros, Catherine; Desdoigts, Alain; Kouadio, Hugues
Abstract: This study sets forth a positive relationship between tenure insecurity and investment over different time horizons among cocoa farmers in Ivory Coast. This positive relationship stands in stark contrast to results found in many related studies. We argue that this difference stems from the types of crops considered and depends, in particular, on whether one considers annual and/or perennial crops. Given that cultivating perennial crops such as cocoa requires large upfront investments over a long period of time, retaining control over land in the long run is essential, especially when the trees reach full maturity. According to some theoretical arguments, investing is a way of retaining such control when the farmer does not have administrative rights. Our results show that cocoa farmers whose status remains precarious in terms of tenure security (migrants) have a higher propensity to invest, especially when the tree is about to yield substantially. This study thus underlines the need to account for the life cycle of crops and the associated revenue streams when assessing the relationship between tenure (in-)security and investment.